Learning Futures – Futures of Learning - Book of Abstracts of the 21st Futures Conference 8–9 June 2021 Online and Turku, Finland - Murphy Jonathon; Saarimaa Riikka (Turun yliopisto, 2022)
As we move further into the 21st century, we need to renew our understanding of what it means to learn, teach, and develop new knowledge. Education systems and learning processes for people of all ages are needed to navigate uncertainty, address known problems, identify new ones, and be able to detect and make the sense of emergent issues and opportunities. The roles of education and learning are also becoming more essential in solving the pressing global ecological, cultural, societal and economic challenges. One pathway for renewal is the development of futures learning at all levels of education and in wider society.
The ‘Learning Futures’ conference creates a cross-disciplinary platform where participants can meet, share, and discuss new ideas concerning futures and learning. The conference program consists of keynote lectures, parallel sessions, participatory workshops and a chaired poster session. The conference will aim to generate multidisciplinary, stimulating and critical discussions that promote networking between people interested in futures issues from different backgrounds.